AN APPLICATION OF GEOGRAPHIC INFORMATION SYSTEM TO ANALYSE POTENTIAL OF POSTAL SERVICE: A CASE STUDY OF KANCHANABURI PROVINCE - อินทรสุวรรณ อรรถพล; เมฆแสงสวย ปกรณ์; มนต์ประภัสสร สถาพร (Journal of Letters, 2018)
According to the 2016 annual report of the Thailand Post Co., Ltd., 80% of the company’s income were derived from e-commerce. The income from this business channel has been increasing steadily, affecting an increasing in workload in many post offices. Kanchanaburi Post Office has been faced with the same problem, which led to ineffective performance such as waiting in a long queue and an insufficient number of post offices. The aim of this research is to evaluate a potential of service of post offices in Kanchanaburi province by using a Geographic Information Systems (GIS). This research applied 4 related factors: the number of deposit services, income from deposit services, coefficient of time for customer’s service per one counter, and population density. Then, these factors have been analyzed by using the Overlay technique. Next, the potential areas were classified into 5 categories following the Equal Interval technique. The results found that the highest potential area was 34.22 square kilometers, covering 3 post offices: Kanchanaburi, Tha Ruea Phra Thaen and Tha Muang. In terms of the number of deposit services and income from deposit services from the study area between 2012 and 2016, it showed that the number of deposit services has been rising consistently. An off-peak period of each year was between February and April. In contrast, the peak period was from October to January. Thus, the researcher suggests that mobile post office services could be implemented into the 3 highest potential areas in order to increase effectiveness of post office services. The mobile post office service has benefits in terms of more accessibility, more mobility, and less cost of operation.